Clarity in Business Contract: An Analysis of Amazon’s Influencer Terms and Conditions - Siregar, Multhahada Ramadhani; Kurnilasari, Dwi Tiara; Naldi, Syafri (International Journal of English Education and Linguistics (IJoEEL), 2025)
This study will examine the accessibility of the Amazon Influencer Terms and Conditions by analyzing some of the semantic ambiguities in the document and how those ambiguities influence the influencer's awareness of rights and obligations. Digital marketing, or influencer marketing in particular, has become a regular way of conducting business in an online world, but the language in those contracts is often still unclear and complicated, especially for someone without a legal background. This study employs qualitative textual analysis, based on semantic theory, in order to uncover lexical, modal, syntactic, and referential ambiguities in the contract. The study found many examples of ambiguity, including vague terms such as “reasonable” and the unexpected use of modal verbs “may” in politically important phrases, which leaves the influencer confused about their duties and the authority of the platform. These uncertainties could make the transparency worse, and consequently can destroy the balance in the relationship between Amazon and its partners. The investigation also emphasizes the need for the usage of clear and simple language and one terminology due to the high level of influence and fair precision in influencer contracts. It is recommended to enhance the functionality of providing full explanations to help readers to be able easier to understand some of the concepts, identical or similar occurrences of modal verbs in legal documents that were intended to act as a legally binding document, and usability testing to identify the readability problems of non-legal readers.